Educational Management Strategies in Improving the Quality of Islamic Educational Institutions - Yovie Djundjunan; Asep Mulyana; Ilman Nafi'a (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Islamic educational institutions are increasingly challenged to maintain and enhance their institutional quality in the context of globalization, technological change, and rising demands for accountability and educational standards. This study aims to analyze and synthesize effective educational management strategies that contribute to improving the quality of Islamic educational institutions. A qualitative approach was employed using a library research design, involving the systematic review of peer-reviewed journal articles, books, and relevant official documents published within the last five years. Data were collected through documentation techniques and analyzed using thematic content analysis to identify recurring patterns and key strategic dimensions.The findings indicate that transformational leadership, strategic planning and curriculum management, quality assurance systems, and stakeholder engagement are critical factors in strengthening institutional performance. In addition, the integration of modern management practices with Islamic values such as accountability, trustworthiness, and collective responsibility enhances both organizational effectiveness and institutional credibility. These results demonstrate that institutional quality improvement is not solely dependent on technical management processes but also on the alignment of administrative practices with ethical and spiritual principles. In conclusion, a holistic and integrative management approach that harmonizes professional standards withIslamic values is essential for achieving sustainable quality improvement in Islamic educational institutions.